The Influence Of Transformational Leadership, Work Engagement On Turnover Intention With Job Insecurity Mediation In Millennial And Z Generations In East Jakarta Construction Companies - Febria Nur Khalilah; Lia Amalia (Journal of Social Research, 2024)
Turnover intention is becoming an increasingly important issue in the world of work in Indonesia. The aim of this research is to analyze the influence of transformational leadership, work engagement, and job insecurity as mediating roles on turnover intention. The data used is primary data sourced from a questionnaire in Google Form which was distributed to Millennial and Z generation employees who work in East Jakarta construction companies. This research was designed using a purposeful sampling method involving 303 respondents with permanent employee status. The data were analyzed using the Structural Equation Modeling (SEM) method. The results in this research prove that transformational leadership and work engagement have a negative influence on turnover intention. Job insecurity can partially mediate between transformational leadership and work engagement on turnover intention. The implications of these findings are the development of motivating leadership, increasing work engagement, and effective management of job insecurity to reduce the intention of Millennial and Generation Z employees to leave the company.